2014
DOI: 10.1589/jpts.26.1521
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships among Vitamin D Level, Balance, Muscle Strength, and Quality of Life in Postmenopausal Patients with Osteoporosis

Abstract: [Purpose] The aim of this study was to examine the relationships among vitamin D levels, balance, falls, muscular strength, and quality of life in patients with postmenopausal osteoporosis. [Subjects and Methods] Forty-six patients diagnosed with postmenopausal osteoporosis and forty-six healthy controls were included in the study. Bone mineral density was determined by DEXA, and functional balance was evaluated the Timed Up and Go (TUG) test, Chair Raising (CRT) test, Berg Balance Scale (BBS). The muscular st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 23 publications
2
28
0
1
Order By: Relevance
“…The current study results showed that participants who were found to have lower level of serum Vitamin D were found to have poor HRQoL. Consistent with the current study finding, Korkmaz et al revealed in a randomised controlled trial that HRQoL was significantly lower in postmenopausal women who had low serum vitamin D than those who had normal vitamin D level. A study conducted by Mastaglia et al showed that vitamin D levels should be ≥20 ng/ml to achieve optimal muscle strength and function.…”
Section: Discussionsupporting
confidence: 88%
“…The current study results showed that participants who were found to have lower level of serum Vitamin D were found to have poor HRQoL. Consistent with the current study finding, Korkmaz et al revealed in a randomised controlled trial that HRQoL was significantly lower in postmenopausal women who had low serum vitamin D than those who had normal vitamin D level. A study conducted by Mastaglia et al showed that vitamin D levels should be ≥20 ng/ml to achieve optimal muscle strength and function.…”
Section: Discussionsupporting
confidence: 88%
“…However, it is noticeable that previous clinical studies on hypovitaminosis D and muscle strength have shown conflicting results [5]. Some cross-sectional studies reported decreased muscle strength in the case of hypovitaminosis D [6,7], although others did not find any significant association [8,9]. Moreover, a meta-analysis of interventional trials showed that vitamin D supplementation could not enhance muscle strength after 9 months of supplementation on average [5].…”
Section: Introductionmentioning
confidence: 99%
“…Um estudo realizado com 46 pacientes do sexo feminino, pós-menopausa, com osteoporose, mostrou similares resultados quanto à força muscular e à qualidade de vida, correlacionadas também a outros fatores de risco para quedas (KORKMAZ et al, 2014).…”
Section: Fatores De Risco Associados a Quedas Em Idosas: Um Enfoque Punclassified